Transoesophageal echocardiography findings in young patients with cryptogenic ischemic stroke. (3rd October 2022) - Hutyra, M; Sanak, D; Kral, M; Dornak, T; Precek, J; Hudec, S; Navratil, K; Kocianova, E; Koubek, F; Kanovsky, P; Taborsky, M
Abstract: Background and purpose: The cause of ischemic stroke (IS) remains often unclear in young patients. Relevant structural heart abnormities with known embolic potential may represent cause of IS also in young population. The use of transoesophageal echocardiography (TEE) allows reliable detection of most relevant structural pathologies. The aim was to assess frequency and spectrum of relevant cardiac abnormities in young IS patients. Subjects and methods: The study set consisted of young acute IS patients <50 years enrolled in the prospective HISTORY (Heart and Ischemic STrOke Relationship studY) study, registered on ClinicalTrials.gov NCT01541163). In all patients, the brain ischemia was confirmed on CT or MRI. Admission ECG, serum specific cardiac markers, TEE, 24-hour and 3-week ECG-Holter were performed in all patients. Results: Out of 1284 patients enrolled in the HISTORY study, 135 (73 males, mean age 40.2±8.1 years) were <40 years. In total, the relevant TEE abnormities were present in 47 (35%) of these patients. Patent foramen ovale (PFO) with evident left to right shunt was detected in 38 (28%) patients, with significant right to left shunt in 25 (19%) patients, and other atrial septal defect with clinically significant bidirectional flow in 4 (3%) patients. Significant valvular heart disease was present in 2 (1%) patients (1 bicuspid aortic valve with moderate aortic regurgitation, 1 chronic severe mitral regurgitation), and 4 (3%) patients severe left ventricular systolic dysfunction (left ventricular ejection fraction ≤35%) due to idiopathic dilated cardiomyopathy. Left atrial myxoma was detected in one patient. Conclusion: The relevant structural abnormities with embolic potential were detected using TEE in 35% of young IS patients. Routine use of TEE to elucidate the causes of stroke, has a role especially in young patients who present with cryptogenic stroke and no cardiovascular risk factors, as well as in the setting of a PFO associated with a deep venous thrombosis. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): IGA LF UP, MH CZ - DRO